The seven storey mountain - Merton, Thomas (Orlando, FL HBJ, 1990)
A fiftieth-anniversary edition of the 1948 spiritual autobiography of Thomas Merton, a young man whose search for peace and faith led him to join the religious order of the Trappist monks
D., 8/2000
Keywords: Merton, Thomas, 1915-1968; Trappists--United States--Biography